Pemberdayaan Pembuatan Pestisida Nabati Menggunakan Daun Pepaya dan Sirsak pada Kelompok Tani Barona, Aceh Tamiang - Cut Mulyani; Arisna Fauzia; Iswahyudi Iswahyudi (Institut Pertanian Bogor, 2026)
The Barona Farmers Group in Seunebok Village, Pidie, is one of the farmers' groups that regularly produces rice in Aceh Tamiang Regency. The main problem frequently encountered by the farmer group is a moderate pest attack that affects almost 50% of the group's land area before entering the vegetative phase. This type of pest is the false whitefly (Cnaphalocrosis medinalis), which is characterized by the presence of caterpillars on the leaves. Therefore, farmers use chemical control methods, which impact the quality of rice yields. Farmers are also still unable to implement pest management using botanical pesticides due to a lack of knowledge in their manufacturing practices. The goal of PKM is to provide sustainable empowerment to farmers by providing training in the manufacture of botanical pesticides by utilizing local potential. These local potentials are papaya and soursop leaves. The method used is participatory, involving the community in direct practice in making botanical pesticides. This activity was held at the Seunebok Village Hall in Pidie with 20 participants. The results of the activity showed an increase in the community's ability to combine the use of natural ingredients, namely papaya and soursop leaves, for botanical pesticides. The results showed an increase in farmers' knowledge regarding rice pests from 65 to 80%, material selection from 33 to 87%, processing methods from 25 to 95%, and application techniques from 10% to 82%. These improvements demonstrate the effectiveness of practice-based training in improving farmers' skills.